2006
DOI: 10.1097/01.brs.0000219876.45640.2a
|View full text |Cite
|
Sign up to set email alerts
|

Goldenhar-Associated Conditions (hemifacial microsomia) and Congenital Deformities of the Spine

Abstract: The prevalence of Goldenhar-associated conditions in patients with congenital spine deformities was 2%. Failures of vertebral segmentation were the most frequent abnormality in the cervical spine, whereas failures of vertebral formation most commonly occurred in the thoracic or thoracolumbar spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…Occurring in an estimated 2.0 to 3.3 per 10,000 live births,2 HFM is characterized by asymmetric underdevelopment of facial structures, including the ear, maxilla and mandible, soft tissues and facial nerves 3–8. HFM is phenotypically heterogeneous, ranging from microtia with mild mandibular asymmetry to Goldenhar Syndrome, which includes vertebral and eye anomalies4,812 and, variably, extracraniofacial anomalies 6,8,10–14.…”
Section: Introductionmentioning
confidence: 99%
“…Occurring in an estimated 2.0 to 3.3 per 10,000 live births,2 HFM is characterized by asymmetric underdevelopment of facial structures, including the ear, maxilla and mandible, soft tissues and facial nerves 3–8. HFM is phenotypically heterogeneous, ranging from microtia with mild mandibular asymmetry to Goldenhar Syndrome, which includes vertebral and eye anomalies4,812 and, variably, extracraniofacial anomalies 6,8,10–14.…”
Section: Introductionmentioning
confidence: 99%
“…The cervical, spinal abnormalities of patients with oculoauriculo-vertebral spectrum are usually hemivertebrae, or spinal segmentation defects. Vertebral fusions have been reported, but without information about whether the fusion is of the blocked type (Klippel-Feil syndrome) or whether there is evidence of progressive, noninfectious anterior vertebral fusion (Willemsen, 1982;Rollnick et al, 1987;Ardinger and Lin, 1988;Van Bever et al, 1992;Van Meter and Weaver, 1996;Goldenhar, 2005;Tsirikos and McMaster, 2006). Fryns et al (1993) reported two possibly affected sibs.…”
Section: Discussionmentioning
confidence: 94%
“…Not infrequently, these vertebral anomalies are associated with the facial malformations leading to the clinical picture of OAVS: a nonexclusive phenotypic spectrum of pathologic entities, which are related to defects of morphogenesis occurring at the same stages of embryologic development. The prevalence of OAVS in cases of congenital spine deformities diagnosed postnatally is 1.25-2%, with thoracic scoliosis being the most common clinical presentation [25,26] . Spinal anomalies described in patients with OAVS include hemivertebrae, occipitalization of the atlas, cuneiform vertebra, platybasia, partial or complete cervical synostosis of more than 2 vertebrae, spina bifida, lumbarization of the sacrum or aplasia of the sacral vertebrae and rib anomalies [27] .…”
Section: Discussionmentioning
confidence: 99%